The meaning of oxidized A-type post-orogenic granitic magmatism: Petrogenesis of the Itupeva Pluton, Itu Batholith, SE Brazil - Monsalve Hernández, Viviana Marcela (2020)
In this work, an integrated study of the petrography, mineral composition, whole-rock geochemistry and Sr-Nd isotopes was carried out for the Itupeva pluton. This pluton belongs to the Itu Batholith, which is the most expressive occurrence of granitic rocks with A-type affinity in the post-orogenic Itu Granite Province, São Paulo, Brazil, and it is mainly composed by granites with subordinate quartz monzodioritic rocks occurring as syn-plutonic dykes and microgranular enclaves. The granites are magnesian, high-K calc-alkaline and metaluminous to slightly peraluminous and classify as oxidized A-type granites. Important geochemical features are an enrichment in large ion lithophile elements (LILEs) and light rare earth elements (LREEs), with negative Eu anomalies (Eu/Eu* = 0.47- 0.58), and a relative depletion in high field strength elements, reflected in negative Nb and Ti anomalies in spidergrams. The associated quartz monzodiorites are metaluminous and have REE-rich patterns that are subparallel to those of the granites, sharing with them some other key geochemical features such as enrichments in Rb, Ba, K and LREE, and depletions in Nb and Ti. Together with similar Sr- Nd isotope signatures, this is suggestive of a comagmatic character for granites and quarz monzodiorites. Macro and microstructural features such as the occurrence as synplutonic dikes and microgranular enclaves with resorbed and mantled quartz and K-feldspar, locally back-veined by granitic material indicate that the quartz monzodiorites crystallized from magma that was injected into and mingled with the granitic mushes at the emplacement level, locally inducing some remelting. The integrated petrology and elemental and isotopic geochemistry suggests that the granites and quartz monzodiorites were generated by the interaction of mantle-derived magmas and crustal melts in the MASH or \"hot\" zone at deep crustal levels. During ascension to shallower crustal levels these magmas entrained antecrysts (e.g., high and low-An plagioclase in quartz monzodiorites, high- Ba biotite in granites) derived from crystal-rich magma reservoirs. In this scenario, we suggest a magma evolution in interconnected crystal-rich magma reservoirs localized in different crustal levels. The compositional and mineralogical variation featured in the Itupeva pluton records multiple processes of magma evolution, including crystallization and accumulation, recharge and remobilization of crystal mushes, magma mixing and mingling, assimilation, and entrainment of antecrysts, which operated along a transcrustal magmatic system.